Partial Peace Rebel Groups Inside And Outside Civil War Settlements - Nilsson, Desirée (The World Bank, 2008)
Previous research proposes that peace is more likely to become durable if all rebel groups are included in the settlement reached. The argument implies that if actors are excluded and continue to pursue the military course, this could have a destabilizing effect on the actors that have signed an agreement. This article argues that all-inclusive peace deals - signed by the government and all rebel groups - are not the panacea for peace that many seem to believe. Given that the parties are strategic actors who are forward-looking when making their decisions, the signatories should anticipate that the excluded parties may continue to fight. Therefore, the risk of violent challenges from outside actors is likely to already be factored into the decision-making calculus when the signatories decide to reach a deal, and so does not affect their commitment to peace. Implications from this theoretical argument are tested using unique data on the conflict behavior of the government and each of the rebel groups in internal armed conflicts during the post-Cold War period. The results are well in line with the theoretical expectations and show that whether an agreement leaves out some actor does not affect whether the signatories stick to peace. The results demonstrate that even when excluded rebel groups engage in conflict, this does not affect the signatories' commitment to peace. Hence, the findings suggest that partial peace is possible